2007
DOI: 10.1021/ac062455y
|View full text |Cite
|
Sign up to set email alerts
|

Top-Down Lipidomic Screens by Multivariate Analysis of High-Resolution Survey Mass Spectra

Abstract: Direct profiling of total lipid extracts on a hybrid LTQ Orbitrap mass spectrometer by high-resolution survey spectra clusters species of 11 major lipid classes into 7 groups, which are distinguished by their sum compositions and could be identified by accurately determined masses. Rapid acquisition of survey spectra was employed as a "top-down" screening tool that, together with the computational method of principal component analysis, revealed pronounced perturbations in the abundance of lipid precursors wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
147
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 179 publications
(152 citation statements)
references
References 38 publications
5
147
0
Order By: Relevance
“…The most detailed analysis presented here required 100 min per sample. We note that the lipidomics platform can be operated with higher sample throughput as required for screening routines simply by lowering the structural specificity of the analysis (31). By monitoring the absolute abundance of individual lipid species we demonstrated that differences in growth temperature and defects in the lipid biosynthesis machinery produced alterations throughout the entire yeast lipidome.…”
Section: Discussionmentioning
confidence: 96%
“…The most detailed analysis presented here required 100 min per sample. We note that the lipidomics platform can be operated with higher sample throughput as required for screening routines simply by lowering the structural specificity of the analysis (31). By monitoring the absolute abundance of individual lipid species we demonstrated that differences in growth temperature and defects in the lipid biosynthesis machinery produced alterations throughout the entire yeast lipidome.…”
Section: Discussionmentioning
confidence: 96%
“…Importantly, GSP profiling remains fully integrated into the shotgun lipidomics pipeline. High mass resolution of an LTQ-Orbitrap instrument enabled unequivocal assignment of species via their m/z , which was determined with a sub-ppm mass accuracy, hence eliminating the need of MS/MS (28,29). Therefore, it has become possible to profile the lipidome of GSPrich MDCK cells (19) and to track the lipidomic changes during epithelial polarization at the level of individual molecular species.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, "top-down" lipidomic approaches in which all structure elucidation occurs on ionized and mass-selected lipids inside the mass spectrometer have rapid throughput and limited sample requirements. However, a current limitation of such approaches is that key structural motifs that may play critical roles in defining the specificity of lipid-protein interactions [19,20] remain unresolved or ambiguous. More specifically, "top-down" techniques cannot readily determine: (1) the position of double bonds within an acyl chain; (2) the stereochemistry of double bond(s) (i.e., cis or trans); and (3) the relative position of acyl chains on the backbone of a complex lipid (i.e., sn-position on a glycerolipid).…”
Section: Krylova Et Al Observed An [M -H]mentioning
confidence: 99%